HERMAPHRODITISM IN Anadara granosa (L.) and Anadara antiquata (L.) (BIVALVIA: ARCIDAE) FROM CENTRAL JAVA - Norma Afiati (JOURNAL OF COASTAL DEVELOPMENT, 2007)
Gonad maturation and sexuality in Central Java populations of A. granosa and A. antiquata were studied by means of macroscopic examination of the visceral mass, microscopic examination of smears of gonadal products and by histological technique. In this study, hermaphrodites occurred extremely rarely, i.e. less than 1.5% for A. granosa and less than 1% for A. antiquata, were observed with both male and female gametes present within the same individual follicles. Unbalanced sex ratios derived from size frequency distribution of the sample revealed that the increased percentage of females with increasing size suggest the occurrence of sequential protandric hermaphrodite with only a single sex change during their life history, i.e. from male to female. The preponderance of juvenile males within the Wedung population should be seen as the advantage of firstly being male, since some energy could be saved and redirected towards somatic growth because in Bivalvia there is a trade-off between growth and reproduction.